Digital government, state modernization and citizen service: Considerations in a digital government strategy in Peru - Rodríguez Alegre, Lino Ronaldo; López Padilla, Rosario del Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective was to analyse the understanding of the importance and priorities of the factors that will contribute to implement digital government in the Regional Government of Lima Provinces. It was an exploratory research of descriptive scope, qualitative approach with documentary review strategy. An association and prioritization between these factors were identified with observance of dependence and interrelation. The Regional Government of Lima Provincias is developing e-government actions and undertaking a digital government strategy requires understanding the importance of the factors and the variables associated with them in order to establish a digitalization strategy.